Qualitative research in a nutshell - Baharom, Anisah; Mohd Zulkefli, Nor Afiah (Community Health Society Malaysia, 2014)
Qualitative study has gained popularity in medical and health research to gain in-depth understanding of individual’s experiences in going through illness and treatment within their contextual environment. This article provides an introduction and overview of qualitative study for basic understanding of this approach of research. It gives a description of the overall process of qualitative methodology in general which includes sampling, data collection, data analysis and writing.